DNA barcoding supports mitochondrial lineage structure in the genus Macaca with implications for biomedical research and laboratory colony management - Lim, Voon Ching; Kanthaswamy, Sree; Malaivijitnond, Suchinda (John Wiley and Sons, 2026)
Background: Cynomolgus macaques are widely used in biomedical research, yet the hybridisation between the subspecies M. f. fascicularis (Mff) and M. f. aurea (Mfa), and introgression from another species M. mulatta (Mm) may affect the research outcomes. Methods: DNA barcoding targeting COI mtDNA, as well as phylogenetic, pairwise distance and statistical analyses were employed to examine the relationships between Mff, Mfa and Mm using 52 newly sequenced and 59 public DNA barcodes representing 17 Macaca taxa and seven species groups. Results: DNA barcoding delineated the Macaca taxa, revealing genetic distinctions between Mff and Mfa greater than between Mff and Mm, as well as delineating geographical populations. This underscores the need for verification of laboratory individuals, besides genetic management of breeding colonies, as genetic differences can influence disease susceptibility and drug trial outcomes. Conclusions: DNA barcoding offers a rapid, cost-effective tool to ensure appropriate selection and genetic management of laboratory individuals used in biomedical research.